Memahami Struktur Keuangan Perusahaan Melalui Analisis Common Size - M, Mursekha; Rosyada, Vika Amarina; Sari, Dwi Mustika (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Common Size Analysis breaks down the figures in the Balance Sheet and Income Statement into percentages based on a specific basis. in general Analysis Common size can be calculated by dividing each account component by the account total, then multiplying the answer by 100%. Components and totals depend of which account is to be analyzed. Performance is work ability demonstrated by work results. A company’s performance is something that a company produces in a given period with reference to set standards.